DISTRIBUTED SENSOR NETWORK FOR SECURITY SYSTEMS - Bykovyy, Pavlo (International Journal of Computing, 2014)
The low-cost network controller for security systems detectors was designed. The controller’s specifics lies in two-wired network interface with the “common bus” topology support. This design reduces the amount of data communication channels from detectors.